Comitê das bacias hidrográficas da região metropolitana de Fortaleza (CBH-RMF): trajetória e desafios para a gestão hídrica participativa - Benevides, Amanda (2011)
The river basin committees - CBH were established in Brazil by Law 9433/97, the National Policy of Water Resources, with the goal of enabling social participation in conducting the process of water management, through the representation of various sectors of society, to discuss and define paths for a given river basin where they live and work. In this context, We made an analysis of the trajectory of the Watershed Committee of the Metropolitan Region of Fortaleza - CBH-RMF, the state of Ceara, in order to understand whether the activities of that committee has been successful in addressing the problems environmental Metropolitan Watershed, and what limitations on the articulation of policies and in the effectiveness of participatory water management. As a basis for the studies we were performed literature searches, analysis of documents, records, interviews and observation of committee meetings. The research concluded that the CBH-RMF has taken relevant steps, especially in making diagnoses and conducting some procedures. However, this policy has limitations in its implementation because it is poorly distributed and discussed with the company. It is necessary to greater institutional coordination and social participation to reflect the views and interests of the community in relation to water management.